A new model for bearing spall size estimation based on oil debris. (April 2022) - Madar, Eyal; Galiki, Ofir; Klein, Renata; Bortman, Jacob; Nickell, Jeremy; Kirsch, Mathew
Highlights: Oil debris monitoring for bearing faults severity estimation. Bearing diagnostics and prognostics. Bearing deterioration process. Validated, comprehensive dynamic model. Physics-based prognostics. Abstract: This paper presents a study on damage severity estimation of spalled bearings based on an Oil Debris Monitoring (ODM). Several failure progression tests on angular contact ball bearings were performed. The spalls formed at the end of the tests were expanded over more then 180 ° of the bearing race. Based on the ODM data analysis, it was possible to discriminate between the three stages of spall growth i.e., initiation, steady-state propagation, and accelerated propagation. A well-established dynamic model of bearings was used to simulate the dynamic behaviour of the angular contact ball bearing with a variety of spall sizes on the inner race. The analysis of the simulated signals from the model revealed that the transition from the steady-state to the accelerated propagation stages occurred at the arc length between two adjacent balls. This finding allowed the development of a new ODM model for spall size estimation in the accelerated propagation stage. The new ODM model relates the loss of mass from a bearing, as measured by an ODM sensor, to the size of the spall in the bearing. The ODM model considers the change in the spall geometry as the bearing deteriorates. The estimated spall size was in good agreement (maximum error of 13%) with the measured spall size at the end of the failure progression tests.